Primary idiopathic hypertrophic osteoarthropathy in a child: characteristics of the disease with a case report - N. A. Lyubimova; L. S. Snegireva; N. A. Terentyev; R. V. Idrisova; V. V. Avramenko; A. I. Imelbaev; O. L. Krasnogorskaya; M. M. Kostik (Современная ревматология)
The paper gives the data available in the literature on the relatively rare disease hypertrophic osteoarthropathy (HOA). This syndrome includes symptoms, such as clubbed fingers (hypertrophy of the distal phalanges), periostosis (subperiosteal new bone formation along the distal diaphysis of the long bones with further progression in the proximal direction) and arthritis, as well as skin changes (pachydermia) that are not an obligate sign. There is information concerning the pathogenesis, clinical, laboratory, and instrumental manifestations of this disease. The paper describes a clinical case of primary HOA in a teenager who has been misdiagnosed with juvenile idiopathic arthritis (JIA). It shows the necessity of including HOA in the spectrum of differential diagnosis in children with articular involvement since HOA may resemble JIA in its clinical manifestations. Patients with primary HOA who have been misdiagnosed with JIA have a long ineffective experience with immunosuppressive and sometimes even glucocorticoid therapies. The specific features that can distinguish the full form of primary HOA from chronic arthritis is the absence of inflammatory changes in the synovial fluid, the presence of clubbed fingers, pachydermia and the lack of morning stiffness.